Semantic Shift in Arabic Vocabulary from Classical to Contemporary Usage: An Analytical Study of Modern Terms - Ghina Hajidah Manaf; Nur Hasan; Muhammad Ichsan (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
Language is an evolving entity shaped by the communicative needs of its speakers. In the context of modern Arabic, changes in word meanings are one form of adaptation to the advancement of time. This study aims to analyze the semantic shifts of five Arabic vocabulary items from the classical to the modern era, identify the types of changes, and explore the underlying causes. A qualitative descriptive approach is employed, using lexical semantic analysis based on literature review. Data were collected by compiling a list of vocabulary items that exhibit meaning shifts, tracing their usage in modern sources, and comparing them with their classical meanings found in secondary references. The primary data source is the modern dictionary Mu'jam al-Ma'ani, while classical meanings are drawn from journal articles as supporting references. The findings reveal that semantic expansion is the most dominant type of change, followed by shift and total change. The contributing factors include technological development, semantic association, and the need for modern terminology. This study highlights that modern Arabic demonstrates a high degree of flexibility in adopting new terms without losing the roots of classical meanings.